Quantitative ecology spatial and temporal scaling - Schneider, David C. (Acad. Press, 1994)
Quantitative Ecology reviews the manifold ways that scale influences the interpretation of ecological variation. Ecologists recognize the significance of scale and magnitude in providing a context for resolution of ecological problems. Written for advanced undergraduates, graduate students, and faculty researchers, this book synthesizes a burgeoning literature on the influences of scale. As scale, magnitude, quantity, and measurement occupy an expanding role in ecology, Quantitative Ecology will be an indispensable addition to individual and institutional libraries.
Keywords: Ecologie; Wiskundige methoden; Écologie - Mathématiques; Mathematik; Ökologie; Ecology -- Mathematics; Quantitative Methode